PENGGUNAAN TEKNOLOGI PENDIDIKAN DALAM PENGAJARAN DI SEKOLAH DASAR: TREN DAN DAMPAKNYA TERHADAP HASIL BELAJAR SISWA - Sarafiah Sarafiah; Abas Oya; Yuyun Yuningsih RS; Eva Nursa'ban (STKIP HARAPAN BIMA, 2024)
This study aims to analyze and identify trends in the use of educational technology in teaching at the elementary school level from 2019 to 2024 and evaluate its impact on student learning outcomes. Using a bibliometric approach, data was collected from Crossref via the Publish or Perish application, focusing on keywords such as